Metformin Improves Insulin Sensitivity and Vascular Health in Youth with Type 1 Diabetes: A Randomized Control Trial - Bjornstad, Petter (Circulation, 2018)
BACKGROUND: Cardiovascular disease (CVD) is the leading cause of mortality in type 1 diabetes (T1D) and relates strongly to insulin resistance (IR). Lean and obese T1D adolescents have marked IR. Metformin improves surrogate markers of IR in T1D, but its effect on directly-measured IR and vascular health in T1D youth is unclear. We hypothesized that 1) T1D adolescents have impaired vascular function, and 2) metformin improves this IR and vascular dysfunction. METHODS: T1D adolescents and controls underwent MRI of the ascending (AA) and descending aorta (DA) to assess pulse wave velocity (PWV), relative area change (RAC), maximal (WSS(MAX)) and time-averaged wall shear stress (WSS(TA)). T1D participants also underwent assessment of carotid intima-media thickness (cIMT) by ultrasound, brachial distensibility (BrachD) by DynaPulse, fat and lean mass by DXA, fasting labs following overnight glycemic control, and insulin sensitivity by hyperinsulinemic-euglycemic clamp (glucose infusion rate/insulin, [M/I]). T1D adolescents were randomized 1:1 to 3 months of 2000 mg metformin or placebo daily, after which baseline measures were repeated. RESULTS: Forty-eight T1D adolescents ages 12–21 years (40% BMI ≥ 90th%ile; 56% female) and twenty-four nondiabetic controls of similar age, BMI and sex distribution were enrolled. T1D adolescents demonstrated impaired aortic health vs. controls, including elevated AA and DA PWV, reduced AA and DA RAC and elevated AA and DA WSS(MAX) and WSS(TA). T1D adolescents in the metformin vs. placebo group had improved M/I (12.2±3.2 vs. −2.4±3.6 [mg/kg/min]/uIU/uL, p=0.005; 18.6±4.8 vs. −3.4±5.6 [mg/lean kg/min]/uIU/uL, p=0.005) and reduced weight (−0.5±0.5 vs. 1.6±0.5 kg, p=0.004), BMI (−0.2±0.15 vs. 0.4±0.15 kg/m(2), p=0.005) and fat mass (−0.7±0.3 vs. 0.6±0.4 kg, p=0.01). M/I also improved in normal-weight participants (11.8±4.4 vs. −4.5±4.4 [mg/kg/min]/uIU/uL, p=0.02, 17.6±6.7 vs. −7.0±6.7 [mg/lean kg/min]/uIU/uL, p=0.02). The metformin group had reduced AA WSS(MAX) (−0.3±0.4 vs. 1.5±0.5 dyne/cm(2), p=0.03), AA PWV, (−1.1±1.20 vs. 4.1±1.6 m/s, p=0.04) and far-wall diastolic cIMT (−0.04±0.01 vs. −0.00±0.01 mm, p=0.049) vs. placebo. CONCLUSIONS: T1D adolescents demonstrate IR and impaired vascular health vs. controls. Metformin improves IR, regardless of baseline BMI, and BMI, weight, fat mass, insulin dose, aortic and carotid health in T1D adolescents. Metformin may hold promise as a cardioprotective intervention in T1D.